Physicochemical characteristics of poly(piperazine-amide) TFC nanofiltration membrane prepared at various reaction times and its relation to the performance - Misdan, Nurasyikin (2015)
Poly(piperazine-amide) thin film composite (TFC) nanofiltration (NF) membranes were prepared via interfacial polymerization (IP) of trimesoyl chloride (TMC) in cyclohexane and piperazine (PIP) in water. The effect of polymerization time on the physicochemical characteristics of poly(piperazine-amide) layers and the final membrane performance was studied in detail. The morphological structures of prepared membranes were investigated using atomic force microscopy (AFM) and field emission scanning electron microscopy (FESEM). Attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR), by contrast, was used to determine the chemical characteristics of the membranes. It is evident that the surface roughness increased with increasing polymerization time due to the formation of a supergranule-like structure over the interfacially synthesized poly(piperazine-amide) layer. Moreover, increasing the polymerization time led to a dramatic reduction of water permeability due to the significant increase of crosslinking poly(piperazine-amide) barrier layers. Experimentally determined data showed that the TFC NF membrane prepared at 10 s of polymerization time experienced 51.2 l/m2.h of water permeability with 97.02% of Na2 SO4 salt rejection at an operating pressure of 0.6 MPa.